PENGARUH DISIPLIN KERJA, GAYA KEPEMIMPINAN, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN B2N DIGITAL FOTOCOPY - Adrie Frans Assa; Anugerah Dachi (Komitmen: Jurnal Ilmiah Manajemen, 2023)
The purpose of this research is to identify and analyze the influence of work discipline on employee performance, the effect of leadership style on employee performance, the effect of work motivation on employee performance, and the influence of work discipline, leadership style, and work motivation on employee performance at B2N Digital Copy. The research method used is to use qualitative methods to explore and understand the meaning that a number of individuals or groups of people ascribe to social or humanitarian issues. The population in this study came from all B2N Digital Copy employees, totaling 20 employees. Collecting data in this study using the interview method. In data processing, this study uses data triangulation. The results of this study indicate that leadership and work discipline affect employee performance. While leadership style can influence employee performance, work motivation does not influence employee performance improvement.